As the inspector said... - Escott, John (Oxford Univ. Press, 1998)
The murder plan seems so neat, so clever. How can it possibly fail? And when Sonia's stupid, boring ;ittle husband is dead, she will be free to marry her handsome lover. But perhaps the boring little husband is not so stupid after all... Murder plans that go wrong, a burglar who makes a bad mistake, a famous jewel thief who meets a very unsually detective... These five stories from the golden age of crime writing are full of mystery and surprises.